Lung transplant recipients on long‐term extracorporeal photopheresis. Issue 10 (1st August 2017) - Isenring, Bruno; Robinson, Cécile; Buergi, Urs; Schuurmans, Macé M.; Kohler, Malcolm; Huber, Lars C.; Benden, Christian
Abstract: Extracorporeal photophoresis (ECP) is an increasingly used therapy to address chronic lung allograft dysfunction (CLAD) following lung transplantation. In 2008, we reported the first single‐center experience showing that ECP not only reduces lung function decline in patients with bronchiolitis obliterans syndrome (BOS) but results in stabilization of patients with recurrent acute cellular rejection (ACR). In this study, the original cohort was followed up further 5 years. In addition, patients with CLAD were retrospectively classified according to recently published phenotypes. The current cohort included 21 of the original 24 patients, of which nine were initially treated for CLAD, 12 were initially treated for recurrent ACR. Our results show that survival of patients treated with ECP for CLAD was inferior to patients treated for recurrent ACR (66% vs. 82% survival rate). Long‐term survivors in the CLAD subgroup were mostly classified as BOS 1 at time of ECP initiation. These long‐term data show that patients started on ECP at early BOS stages have better long‐term outcome. The subgroup of ECP patients with recurrent ACR has an overall superior survival. To assist prediction of therapy response, we agree with other authors that patients with CLAD should be aimed to be phenotyped and evaluated for an early treatment with ECP.